Pendidikan Akhlak Menghargai Perbedaan melalui Learning Community di Maiyah Gambang Syafaat Semarang - Muhammad Nabhan Fajruddin; Nasirudin (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to describe the implementation of moral education respecting plurality in the learning community at Maiyah Gambang Syafaat Semarang. The research is directed at the question: how moral education respect plurality is carried out. This type of reaserch is a qualitative field. Data analysis using descriptiv.The finding of this study are moral education respecting plurality is carried out through community learning, spirituality and the cultivation of values. Those values are humility, togetherness, respect for others and the philosophy of love.The learning community implies a consept that no one is higher and smarter. Spiritualiy will create a sense of love for othersHumility is instilled through a consep that all participats are equal, there is no relationship between teacher and student. The value of togetherness is instilled with awareness with Allah, Prophet Muhammad and creatures.